Decolorization by Catalytic Ozonation USING Mn(II) Fe(II) and Fe(III) - Wonglertarak , Watcharapol; Wichitsathian , Boonchai; Yimrattanabavorn , Jareeya (International Journal of Membrane Science and Technology, 2023)
The textile industry holds significant importance in Thailand. It has been estimated that 10-20% of dyes are lost during the dyeing process and subsequently released into wastewater. The high concentration of non-biodegradable substances in these wastewaters makes them challenging to treat using conventional methods. Therefore, this study aimed to assess the effectiveness of a catalytic ozonation process employing Mn(II), Fe(II), and Fe(III) for treating synthetic dye wastewater. The study also sought to optimize operational parameters such as pH and contact time. Both with and without catalytic ozonation, experiments were conducted in a batch reactor with a consistent ozone flow rate of 6 g/hr. Under the non-catalytic ozonation conditions, it was observed that more than 90% of decolorization occurred within 15 minutes at a pH of 9. The ozonation of the dye followed a first-order reaction mechanism at room temperature, with a rate constant (k) of 0.18 min-1. The catalytic ozonation used a concentration of 1.2 mM of Mn(II) was showed color removal of 90% in 8 min. For catalytic ozonation used Fe(II) and Fe(III) with concentrations of 0.6 mM showed color removal of 90% in 10 min. The highest rate constant (k) showed 0.29 min-1 for Mn(II) and 0.21 min-1 for Fe(II) and Fe(III). In conclusion, the study found that the inclusion of a catalyst substantially enhanced the degradation efficiency of the dye compared to ozonation without a catalyst.